The rock cycle - Superstone, Herb; Miller, Eric (Fort Collins : Scott Resources Inc., 1990)
This video unravels the complex processes that create, change and break down earth materials. Geologist Eric Miller hosts this informative program, taking the viewer on an exiting field trip through the Rocky Mountains. Along the way, each of the three major rock types- igneous, sedimentary, and metamorphic are clearly defined using examples from mountain outcrops and streamside sediments
Keywords: Rocks; Sedimentation and deposition